Dinâmica do fluxo sanguíneo folicular em vacas nelore submetidas a protocolos de IATF - Scaliante Júnior, João Ricardo (2015)
This study aimed to characterize the blood follicle perfusion in 3 fixed-time artificial insemination protocols. Twenty one Nelore cows, randomly divided into three FTAI protocols in a crossover model with a 30 days interval, were used. The BED9 protocol consisted of an intravaginal progesterone implant Sincrogest® and 2 mg of BE IM in D0; implant removal and 150μg IM PGF2α (D-cloprostenol) in D8, and 1 mg of BE IM in D9; BED8 protocol consisted of a P4 implant and 2 mg BE in D0; removal of the implant, 150μg of PGF2α and 1 mg BE in D8; CED8 protocol consisted of na P4 implant and 2 mg BE D0, removal of the implant, 150μg of PGF2α and 1 mg CE in D8. The group of cows was evaluated with ultrasound Color Doppler (MyLab 30GoldVET, Italy) at 3 hours intervals in the first three manipulations and then with 6 hours intervals until ovulation occurs or a maximum of 90 hours, after implant withdrawal. For follicle vascularization was used a subjective rating of degree 1 to 5, which considers the percentage of vascularization in the follicle wall. There was difference (P<0.05) in ovulation time after P4 withdrawal, wich BED8 (64.36 ± 10,42h) anticipated ovulation comparing with the other two treatments, being BED9 (74.40 ± 3,04h) and CED8 (72.00 ± 6,63h) equal. The average size of the pre-ovulatory follicles were similar in the three protocols (p=0.0708). The ovulation rate was lower in BED8 protocol (52.38%), and BED9 (80.95%) and CED8 (90.47%) were similar (p=0.3778). In the three protocols, all animals had a degree 1 follicle at the beginning of evaluation; all ovulatory follicles had degree 5 before ovulation time and this occurred in 12 hours. It was observed that the follicle has the growth rate inversely proportional to the increase of vascularization grade. The Color Doppler tool can examine the vasculature in the follicle wall as predicting the approach of ovulation.